MPTP Neurotoxicity and Testosterone Induce Dendritic Remodeling of Striatal Medium Spiny Neurons in the C57Bl/6 Mouse - Eleni Antzoulatos; Michael W. Jakowec; Giselle M. Petzinger; Ruth I. Wood (Parkinson's Disease)
Nigrostriatal damage is increased in males relative to females. While estrogen is neuroprotective in females, less is known about potential protective effects of testosterone in males. We determined if castration enhances neuronal injury to 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP). Castrates or sham-castrated mice were sacrificed 1 week following injection of MPTP (4×20 mg/kg) or saline (n=11-12/group). The right striatum was immunostained for tyrosine hydroxylase (TH). The left hemisphere was stained by Golgi Cox to quantify neuronal morphology in medium spiny neurons (MSNs) of the dorsolateral striatum. MPTP reduced TH, but there was no effect of castration and no interaction. For MSN dendritic morphology, MPTP decreased the highest branch order and increased spine density on 2nd-order dendrites. Castrated males had shorter 5th-order dendrites. However, there was no interaction between gonadal status and MPTP. Thus, castration and MPTP exert nonoverlapping effects on MSN morphology with castration acting on distal dendrites and MPTP acting proximally.